From information to immunization: the information processes and practices of COVID-19 vaccination implementers and receivers in a Philippine local government unit - Jequinto, Paul Martin
This study sought to a) characterize the information practices and processes of COVID-19 vaccination implementers and receivers in a Philippine Local Government Unit (LGU), b) determine the perceptions and experiences of COVID-19 vaccination implementers and receivers, and c) identify the barriers faced by COVID-19 vaccination implementers and receivers. This study focuses on the grassroots execution of the COVID-19 vaccination in Las Piῆas City, an LGU in the National Capital Region (NCR). This is a descriptive research with data gathered using a semi-structured interview for vaccine implementers and a survey for vaccine receivers.